THE IMPACT OF USING ICT IN TEACHING SOCIAL SCIENCE FIELD TO THE FIFTH GRADE STUDENTS OF SD NEGERI KEUNE KABUPATEN PIDIE - Andayani; Siti Mayang Sari; Akmaluddin; Rahmattullah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to determine whether there is a statistically significant difference between students who get social science field instruction using ICT and those who receive science natural field instruction without using ICT. Quantitative research is used in the conduct of this study. This study's methodology is a quasi-experiment. This design treats the experimental group while doing nothing for the control group. The purpose of this treatment is to test the effects of a certain treatment. The pupils at SD Negeri Keune in fifth grade during the academic year 2022–2023 make up the population of this study. There are 48 students in total, divided into the courses V1 and V2, which total 48. Since there were only two fifth grade classes, those pupils were used as the sample for this study, with class V2 students serving as the experiment group and class V1 children serving as the control group. Each cohort included 24 pupils. The Mann-Whitney test was used to examine the obtained data. The Mann-Whitney test result reveals that the Mann-Whitney U test's Sig. (2-tailed) value is 0.000. It indicates that using ICT to teach social science to SD Negeri Pucok Pulu fifth graders has been successful in enhancing the students' capacity to master the subject.